The establishment - Fast, Howard 1914-2003 (Houghton Mifflin, 1979)
Sequel to "Second Generation." Barbara Lavette is caught up in a chain of events that involve her in a confrontation with Congress during the time of the McCarthy investigations.
Keywords: Domestic fiction; Italian Americans -- Fiction; French Americans -- Fiction; Large type books; San Francisco (Calif.) -- Fiction; Historical fiction; Western stories